The oldest Rhantus (Coleoptera, Dytiscidae) from the earliest Eocene Fur Formation, Denmark - Prokin, Alexander A.; Hájek, Jiří; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2024)
†Rhantus villumi sp. nov. is described and illustrated on the basis of a single specimen from the earliest Eocene Fur Formation, Denmark. With an estimated age of ca. 55.4 Ma, it represents the oldest member of an extant genus of the family Dytiscidae. However, the presence of Rhantus in the early Eocene is only slightly older than previous estimates, and generally agrees well with phylogenetic analyses of the subfamily Colymbetinae. The presence of a predominantly temperate genus in the presumably warm Lagerstätte is briefly discussed, supporting the hypothesis of temporary cooling, as suggested by several other invertebrate records from the Fur Formation. It is suggested that the new species could feed on mosquito larvae, which are known from the Lagerstätte. Finally, a record of another Dytiscidae species from the same locality is mentioned, but, due to poor preservation and lack of diagnostic characters, this fossil remains unidentified to genus or species level.